Sites of violence : gender and conflict zones - Giles, Wenona Mary, 1949-; Hyndman, Jennifer (University of California Press, 2004)
In conflict zones from Iraq and Afghanistan to Guatemala and Somalia, the rules of war are changing dramatically. Distinctions between battlefield and home, soldier and civilian, state security and domestic security are breaking down. In this especially timely book, a powerful group of international authors doing feminist research brings the highly gendered and racialized dimensions of these changes into sharp relief. In essays on nationalism, the political economy of conflict, and the politics of asylum, they investigate what happens when the body, household, nation, state, and economy become sites at which violence is invoked against people. In particular, these hard-hitting essays move us forward in our understanding of violence against women-how it is perpetrated, survived, and resisted. They explore the gendered politics of ethno-nationalism in Sri Lanka, the post-Yugoslav states, and Israel and Palestine. They consider "honor killings" in Iraqi Kurdistan, armed conflict in the Sudan, and geographies of violence in Ghana. This volume augments feminist analysis on conflict zones and contributes to transnational coalition-building and feminist organizing.
Keywords: Violence.; Political violence.; Social conflict.; Women -- Crimes against.; Sex role.; Sex differences.; Feminist theory.; Violence politique.; Conflits sociaux.; Femmes -- Crimes contre.; Rôle selon le sexe.; Différences entre sexes.; Théorie féministe.; violence.; terrorism.; sex role.; social conflict.; SOCIAL SCIENCE -- Violence in Society.; SOCIAL SCIENCE -- Gender Studies.; Feminist theory; Political violence; Sex differences; Sex role; Social conflict; Violence; Women -- Crimes against; Feminismus; Frau; Gewalt; Politik; Politischer Konflikt; Geweld.; Etnische conflicten.; Vrouwen.; Sekserol.; Aufsatzsammlung.